Perancangan Sistem Informasi Akademik Berbasis Web Pada SMAS Islam Darul Fikri Muaro Jambi - Arliana Fadillah Putri Hari Wijaya; Mutamassikin Mutamassikin; Heru Kurniawan (Pusat Riset dan Inovasi Nasional, 2025)
The rapid development of information technology plays a significant role in supporting various fields, including education. However, at SMAS Islam Darul Fikri Muaro Jambi, academic data management is still handled manually, leading to inefficiency, delays, and the risk of data loss. Therefore, this research aims to design and develop a web-based academic information system to address these issues and facilitate the management of academic data such as student records, grades, schedules, and academic reports. The research employs a qualitative method, with system design following the Agile Development model, which consists of several stages: planning, design, coding, release, and feedback. The planning stage involves identifying user needs through observation and interviews. The design stage focuses on creating system workflows and database structures. The system is implemented during the coding stage, and in the release stage, the system is deployed to the domain https://mestongdarulfikri.my.id. Functionality testing using black box testing confirmed that all features work as expected. The system feasibility test resulted in a score of 86.25%, classified as very feasible. This system allows the school to manage academic data more efficiently, quickly, and accurately while improving the accessibility of information for students and parents